Between Sense and Meaning: In Relation to Frege, Can We Form an Alternative Way of Distinguishing Between Sense and Meaning? - Regovec, Matjaž (Analiza: časopis za kritično misel, 2025)
How can one determine a difference between Sense and Meaning? Is there an alternative to the way of differentiation between Sense and Meaning as being used by one of the fathers of modern analytic philosophy, Gottlob Frege (1848–1925), whereby we think his well-known finding that »whereas the sense of the Morning and the Evening Star is different, their meaning is the same«? The organon that we developed comprises some descriptions of the thinking, bodily, and intuitive cogito. The differentiation among the inherent systems of organization and functioning of the three kinds of cogito shows that an alternative description of differentiation between the typical products of the thinking (sense) and the intuitive cogito (meaning) can be ascertained. This is a differentiation between Sense and Meaning that is different from the one in Frege.
Keywords: sense; meaning; cogito; thinking; intuition